Friday Writes: An Exercise in the Believing Game - Stephanie Paterson (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
I introduce the basic principles for the practice of proprioceptive writing and describe the experience and outcomes of incorporating this ungraded writing into three undergraduate compostion classes. I offer this as a case study of a writer, teacher, and reflective practitioner emboldened by Peter Elbow's believing game, and I point out some of the intellectual and pedagogical discoveries that emerged in my fourteen-week experiment.